PENERAPAN AKUNTANSI ZAKAT, INFAQ DAN SHADAQOH PADA LEMBAGA AMIL ZAKAT, INFAQ DAN SHADAQOH DOMPET DHUAFA REPUBLIKA BERDASARKAN PSAK 109 - Wahyudini Syafitri; Rahmat Daim Harahap; Nadila Mifta Mayrani; Silva Zahra Azizah; Mardiah Hasibuan; Pamatua Raja H (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
This study aims to reconstruct the financial statements of zakat, infaq and shadaqoh in Dompet Dhuafa Republika, so that it can be seen how the financial statements of Dompet Dhuafa are recorded and reveal the financial statements of zakat, infaq and shadaqoh. This research uses qualitative descriptive method using secondary data in the form of financial statements from Dompet Dhuafa Republika and related journals. Transparency and accountability in zakat, infaq and shadaqoh financial statements are analyzed based on PSAK 109 which consists of five components of financial statements, namely statements of financial position, changes in funds, assets under management, cash flow statements, and notes to financial statements. It was concluded that the form of Zakat, Infaq and Shadaqoh financial statements on Dompet Dhuafa Republika was not in accordance with the applicable standards, namely PSAK 109, where the financial statements of Dompet Dhuafa Republika did not have records of financial statements.